ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN BISNIS PADA UMKM ZHAFIRA POPCORN - Eriana Saprida; Suhada Suhada; Syfa Tasya Zahwani; Abdul Hafiz; Nurbaiti Nurbaiti (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
This study aims to analyze the factors that influence business success in Small and Medium Enterprises (SMEs), with a focus on Zhafira Popcorn SMEs. The methodology used is descriptive qualitative which uses semi-structured interviews to explore the perceptions and experiences of business owners.. The results showed that business success is influenced by internal and external factors. Internal factors include strong entrepreneurial characteristics, effective leadership, and competent human resources. On the external side, government support and market understanding are key. This study recommends that Zhafira Popcorn improve capital management, conduct product innovation, and utilize technology in marketing to increase competitiveness in the market.